Pump‐Probe Fragmentation Action Spectroscopy: A Powerful Tool to Unravel Light‐Induced Processes in Molecular Photocatalysts. Issue 20 (1st March 2017) - Imanbaew, Dimitri; Lang, Johannes; Gelin, Maxim F.; Kaufhold, Simon; Pfeffer, Michael G.; Rau, Sven; Riehn, Christoph
Abstract: We present a proof of concept that ultrafast dynamics combined with photochemical stability information of molecular photocatalysts can be acquired by electrospray ionization mass spectrometry combined with time‐resolved femtosecond laser spectroscopy in an ion trap. This pump‐probe "fragmentation action spectroscopy" gives straightforward access to information that usually requires high purity compounds and great experimental efforts. Results of gas‐phase studies on the electronic dynamics of two supramolecular photocatalysts compare well to previous findings in solution and give further evidence for a directed electron transfer, a key process for photocatalytic hydrogen generation. Abstract : Pump‐probe action spectroscopy : The combination of ion trap mass spectrometry with ultrafast laser spectroscopy allows reliable access to intrinsic photo‐induced dynamics of (supra)molecular catalysts. The multi‐exponential excited‐state population dynamics and anisotropy relaxation of the complexes give strong support for a fast and directed electron transfer to the catalytic metal center, a key process for their photocatalytic activity towards hydrogen generation.